The improved storage properties of C12A7:Tb3+ X-ray phosphors via Sr2+ doping. (October 2017) - Li, Shengnan; Liu, Chunguang; Zhu, Hancheng; Yan, Duanting; Xu, Changshan; Liu, Yuxue
Graphical abstract: For Sr doped C12A7:0.5%Tb 3+ X-ray phosphors with unique nanocage-like structure, high-quality X-ray imaging (15 lp/mm) was realized under a lower dose (0.96 Gy), suggesting that they are possible to be used for computed radiography system or erasable/rewritable optical memory media. Highlights: C12A7:0.5%Tb 3+, x %Sr 2+ X-ray phosphors were prepared by a combustion method. After Sr doping the X-ray absorption capacity and dynamic range were improved. The maximum conversion efficiency of these phosphors can reach to 1.42 pJ/mm 2 /mR. Sr doping led to the increased trap depths and widths of these phosphors. High-quality X-ray imaging was realized under a lower X-ray dose (0.96 Gy). Abstract: C12A7:0.5%Tb 3+, x %Sr 2+ X-ray phosphors with various concentrations were prepared by a combustion method. For the phosphor with the optimal concentration ( x = 5), the strongest green photostimulated luminescence (PSL), originating from the 5 D4 - 7 F5 transition of Tb 3+ ion, can be achieved. It was found that its X-ray absorption capacity was increased and its X-ray dynamic range was extended after Sr doping. For this phosphor, the conversion efficiency (CE) (∼1.42 pJ/mm 2 /mR) is higher than that of C12A7:0.5%Tb 3+ phosphor (∼1.28 pJ/mm 2 /mR) because of the substitution of Ca by Sr with higher atomic number. Meanwhile, for the Sr doped C12A7:0.5%Tb 3+ X-ray phosphors, the change in the local environment near the electrons captured by the enlarged empty cages will lead to the variation in the trap distribution. High-quality X-ray imaging (15 lp/mm) of the X-ray phosphor suggests that it is a potential candidate material for computed radiography system or erasable/rewritable optical memory media.